2019
DOI: 10.1007/s00436-019-06451-2
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 antibodies from patients with asymptomatic bancroftian filariasis inhibit the binding of IgG1 and IgG2 to C1q in a Fc-Fc-dependent mechanism

Abstract: A striking feature of lymphatic filariasis (LF) is the clinical heterogeneity among exposed individuals. While endemic normals (EN) remain free of infection despite constant exposure to the infective larvae, a small group of patients, generally microfilaria free (Mf-) develops severe pathology (CP) such as lymphedema or hydrocele. Another group of infected individuals remains asymptomatic while expressing large amounts of microfilariae (Mf+). This Mf+ group is characterized by an immune-suppressed profile with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…IgG4 may arise to compensate for the pro-inflammatory activity of agalactosylated glycans that accumulate in active inflammatory diseases. In chronic parasitic infections, IgG4 levels are elevated in individuals with asymptomatic parasitic worm infection compared to symptomatic patients, and this IgG4 has been linked to immune-suppressed states ( 72 ) and blocking of antibody-mediated hypersensitive responses in basophils ( 66 ). IgG4 tend to exhibit enhanced antigen-affinity ( 73 , 74 ); thus, IgG4 may outcompete binding of functional TB-specific antibodies in immune complexes, thereby diminishing antibody effector activity.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4 may arise to compensate for the pro-inflammatory activity of agalactosylated glycans that accumulate in active inflammatory diseases. In chronic parasitic infections, IgG4 levels are elevated in individuals with asymptomatic parasitic worm infection compared to symptomatic patients, and this IgG4 has been linked to immune-suppressed states ( 72 ) and blocking of antibody-mediated hypersensitive responses in basophils ( 66 ). IgG4 tend to exhibit enhanced antigen-affinity ( 73 , 74 ); thus, IgG4 may outcompete binding of functional TB-specific antibodies in immune complexes, thereby diminishing antibody effector activity.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation and contraction of the response is induced by target-related outputs such as the elimination of target cells, target densities dropping below the amplification threshold or inhibition by regulatory molecules expressed on the target or effector cell or recruited from plasma. Similarly, systemic regulation can occur when there is a shortage of effector molecules or cells, or by the presence of interfering immunoglobulin subclasses 29 31 . Conversely, insufficient regulation may cause autoimmunity through excessive or constitutive activation of the antibody functional response.…”
Section: The Role Of Avidity In Antibody Biologymentioning
confidence: 99%
“…Until now the role of CD4 + T cells during L. sigmodontis infection was only elucidated in BALB/c mice (41) and thus this study showed to our knowledge the first time the crucial role of CD4 + T cells for anti-filarial immunity in C57BL/6 mice. Since information about the role of adaptive immune cells for antifilarial immunity in C57BL/6 mice is missing, further experiments should elucidate also the role of B cells by using the established adoptive cell transfer model in RAG2IL-2Rgdeficient mice, especially since B cells have been shown to be important for the immunity in BALB/c strains (42) and distinct immunoglobulin patterns have been shown to be induced during human filarial infection that are crucial for the regulation of host immunity (11,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%